Utilization of the Canva Application for Elementary School Learning Media - Hidayati, Rita; Thomas, Villeda; Luciani, Chasson (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2023)
The purpose of this research is to develop learning media using the Canva application in elementary schools, for beginners and teachers in elementary schools which are used to create multimedia-based learning media as teaching materials that are used at this time, the decreasing quality of learning at this time especially in among the elementary school level, it is on this occasion that we explain the use and use of the Canva application, the aim is to increase the interest and sympathy of teachers and students in learning and also to facilitate the process of understanding student learning in schools so that it can be said that the quality of education in elementary schools is perfect. This Canva application has several interesting features to offer including ready-to-use templates, icons and illustrations, text, background tips and tricks for using applications, animations and duplication, as time goes by and the use of technology depends on ourselves to use it.